1981
DOI: 10.1002/hep.1840010202
|View full text |Cite
|
Sign up to set email alerts
|

Woodchuck hepatitis and hepatocellular carcinoma: Correlation of histologic with virologic observations

Abstract: The livers of 33 captive woodchucks were examined histologically in 30 biopsy and 10 autopsy specimens and the findings were correlated with serum determinations for woodchuck hepatitis virus (WHV), surface antigen (WHsAg) and antibody (anti-WHs), and WHV DNA and DNA polymerase. The liver appeared normal in all 3 serum-negative animals, 7 of 16 with indeterminate WHV status, and 1 of 4 with anti-WHs, but not in 10 animals with WHsAg, WHV DNA, and DNA polymerase. Mild hepatic inflammation was found in 7 woodchu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 19 publications
6
60
1
Order By: Relevance
“…Although it has been suggested that peritumoral necroin ammation plays a promoting role in carcinogenesis (Popper et al 1981, Frommel et al 1984, Popper et al 1987, Gouillat et al 1997), our ndings demonstrate that HCC develops in chronically WHV-infected woodchucks independently of the intensity of necroin ammatory activity. Previous studies of the peritumoral parenchyma in woodchucks have not demonstrated a microscopic pattern of cirrhosis (Snyder 1968, Tyler et al 1986, Popper et al 1987, Gouillat et al 1997, even if a signi cant degree of brosis surrounding portal spaces and sinusoids has been reported (Nada et al 1997).…”
Section: Discussioncontrasting
confidence: 57%
“…Although it has been suggested that peritumoral necroin ammation plays a promoting role in carcinogenesis (Popper et al 1981, Frommel et al 1984, Popper et al 1987, Gouillat et al 1997), our ndings demonstrate that HCC develops in chronically WHV-infected woodchucks independently of the intensity of necroin ammatory activity. Previous studies of the peritumoral parenchyma in woodchucks have not demonstrated a microscopic pattern of cirrhosis (Snyder 1968, Tyler et al 1986, Popper et al 1987, Gouillat et al 1997, even if a signi cant degree of brosis surrounding portal spaces and sinusoids has been reported (Nada et al 1997).…”
Section: Discussioncontrasting
confidence: 57%
“…Considerable interest has been paid to WHV. This is because: (i) genome shares approximately a 60% nucleotide sequence identity with its human counterpart, and (ii) all of the WHV carrier woodchucks succumb to HCC after 2-4 years (Popper et al, 1981;Popper et al, 1987). …”
Section: Hepadnavirus Family and Animal Modelsmentioning
confidence: 99%
“…Studies of the WHV infection showed that this virus is even more potent than HBV as a hepatic carcinogen. Nearly 100% of woodchucks that are infected from birth with WHV will develop HCC, starting at around 18 to 24 months of age (Popper et al, 1981;Popper et al, 1987). Further, ground squirrels that are infected with GSHV will also display an increased prevalence of HCC, though the tumors are less frequent and arise later in life (Marion et al, 1986).…”
Section: Hepadnaviral Infection and Hccmentioning
confidence: 99%
“…For example, ground squirrels infected with ground squirrel hepatitis virus (GSHV) show little evidence of hepatitis (Marion & Robinson, 1983). Woodchucks chronically infected with woodchuck hepatitis B virus (WHBV) often show signs of moderate to severe hepatitis, but the development of cirrhosis as seen in man has not been found (Popper et al, 1981). These differences appear unrelated to the level of virus in the blood, as infected ground squirrels often show very high concentrations of virus (Marion et al, 1980) and indeed HBV infection in chimpanzees may also result in virus levels far in excess of human cases of acute HBV, despite the relatively minor histological abnormalities in infected non-human primates (Zuckerman et al, 1979).…”
Section: Pathogenesis and Serological Propertiesmentioning
confidence: 99%